2022
DOI: 10.1186/s12889-022-12559-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between screen time among children and lower economic status during elementary school closures due to the coronavirus disease 2019 pandemic

Abstract: Background This study aimed to examine whether the extended use of a variety of digital screen devices was associated with lower economic status and other environmental factors among Korean elementary school children and their caregivers during school closures precipitated by the coronavirus disease 2019 (COVID-19) pandemic. Methods A total of 217 caregivers of children 7–12 years of age from Suwon, Korea, were recruited and asked to respond to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…The current study found no significant relationship between parental educational level, marital status, or monthly income and technology use. This finding contradicts a recent study where children from lower-income households used smartphones and tablets more frequently and for longer periods than those from higher-income households [ 33 ]. Another significant finding was that most children who remained on their devices for 6 hours or longer were boys.…”
Section: Discussioncontrasting
confidence: 99%
“…The current study found no significant relationship between parental educational level, marital status, or monthly income and technology use. This finding contradicts a recent study where children from lower-income households used smartphones and tablets more frequently and for longer periods than those from higher-income households [ 33 ]. Another significant finding was that most children who remained on their devices for 6 hours or longer were boys.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are consistent with the results of previous studies showing that the low-income class was vulnerable to media overuse, sleep problems, and problematic behavior. 15 25 34 36 Family income, not only parental wellbeing, but access to an abundant resource of structured education and activity, is an important factor in establishing and maintaining a family's effective coping strategy. 37 However, how income affects other variables during COVID-19 needs to be investigated in detail through additional research.…”
Section: Discussionmentioning
confidence: 99%
“…Screen time was investigated by asking primary daytime caregivers to report the frequency per week and time per day of their children’s screen time including television (TV), tablet personal computer (PC), and smartphone in line with the recommendations of previous studies. 13 25 According to the frequency of use, a request was made to select the number of days each device was used for 1 week. The response options for the mean length of time per day the media were accessed, and the corresponding coded scores were as follows: none (score: 0; less than 1 hour (score: 1); more than 1 hour and less than 2 hours (score: 2); more than 2 hours and less than 3 hours (score: 3); more than 3 hours and less than 4 hours (score: 4); and more than 4 hours (score: 5).…”
Section: Methodsmentioning
confidence: 99%
“…Another large-scale national survey showed child's age, race, parental education, and marital status had significant effects across most types of media [11]. Maternal education, employment, household income and type of care provider were also among the significant predictors quoted in previous studies [12,13]. Environmental factors significantly associated with excessive screen time among younger children were less number of outings and households with no outdoor equipment [14].…”
Section: Introductionmentioning
confidence: 90%